Influence of soil physicochemical properties on biometrical and physical features of persian oak wood - Dong, Huijun; Dahmardeh Ghalehno, Mohammad; Bahmani, Mohsen; Ghehsareh Ardestani, Elham; Fathi, Leila (Maderas. Ciencia y Tecnología, 2022)
This article investigates the relationships between soil characteristics (physical and chemical) and wood properties of Persian oak in three different elevation sites. For this purpose, 27 trees were randomly chosen and cut in Zagros forests in western Iran. The test samples were prepared at the stem (breast height) to examine physical and biometrical properties. For each elevation site, four soil samples were obtained at a 0-20 cm soil depth under the canopy of each tree to measure soil properties, including clay, silt soil, sand soil, electrical conductivity, pH, nitrogen, phosphorus, potassium, and organic matter content. Then, the relationship of soil and wood properties was determined by principal component analysis. Results specified that there are a positive correlation between wood density and volumetric swelling with clay and available potassium. Moreover, the results revealed a positive correlation between fiber length, cell wall thickness, and fiber diameter with electrical conductivity, sand percentage, and total nitrogen content, respectively.